Respon pertumbuhan dan hasil tanaman jagung akibat perlakuan pupuk organik cair papua nutrient dan sistem budidaya - Baso Daeng; Rizald Hussein (Fakultas Pertanian Universitas Papua, 2021)
Corn are one of the leading food crop commodities. Corn, like plants in general, requires nutrients that are absorbed from the soil. One of the potentials of reliable organic fertilizers to support the Go Organic program is the utilization of liquid organic phosphate fertilizer